Life Cycle Assessment of a Municipal Wastewater Treatment Plant Using Simapro 9 Software Tool - Preliminary Results - Giuseppe Mazziotti di Celso; Federico Cecchini; Valentina Innocenzi; Karima Ayedi; Marina Prisciandaro (Chemical Engineering Transactions)
Wastewater treatment plants are powerful tools not only to protect human health and the environment from diseases, but they can also produce effluents that can be released in superficial/groundwater aquifers or reused for different purposes (civil, industrial, agricultural). If properly designed and managed, these plants can contribute to mitigating the effects of global warming, which is the principal cause of water scarcity. This problem is affecting more and more countries, as the CO2 emissions in the atmosphere are still increasing significantly. On the other side, care must be paid to evaluate the environmental impact of these plants. They need energy to correctly work and chemical additives to favour the precipitation of some pollutant species; furthermore, they produce solid waste, the sludge, which must be properly disposed of, without forgetting the emissions that, in some cases, must be treated before being released into the atmosphere. The challenge is to achieve high-quality water but, in the meantime, to perform a process that is not high-energy and high-chemical consuming. Life Cycle Assessment (LCA) is a formidable approach that permits the evaluation of the environmental impact of whatever industrial process, service, or agricultural practice. This tool can be successfully applied to wastewater treatment plants, too. In particular, in this paper, the commercial software SimaPro 9 will be used, together with the CML-IA method and Ecoinvent database (updated to the 3.10 version), to evaluate the LCA of a wastewater treatment plant, which produces an effluent to be reused for irrigation. The leading environmental indicators for global warming, eutrophication, and acidification will be computed for this case study.